Surgeons' personality, characteristics and presence of meaning in life - El Boghdady Michael; Ewalds-Kvist Béatrice Marianne (Elsevier Ltd, 2025)
BACKGROUND
Surgeons work long shifts and are frequently on call. Pressure to make quick and accurate decisions along with the responsibility of performing complex procedures contribute to surgeons' high stress-levels, anxiety and altered empathy level. We aimed to study surgeons' personality and meaning in life at two different centres.
METHODS
General surgeons completed 47 questions. Visual analogous scale-items with controlled internal consistency (Cronbach alpha) coefficients varying from .77 to .85 were used from the following scales: Global Measure of Perceived Stress; Hostility Questionnaire; Jefferson Scale of Physician Empathy; Meaning in Life Questionnaire-SF; Rosenberg Self-Esteem Scale; Spielberger State Anxiety Scale and Quality of Work life Scale. Multiple linear regression analyses, parametric or non-parametric tests were employed when considered adequate.
RESULTS
Fifty-four participants were recruited from 3 different levels of training. Gender differences in Anxiety, Physician Empathy and presence of meaning in life (MIL-P) were revealed. Junior trainees differed from senior trainees and consultants as regards MIL-P, Anxiety, Stress and work-related factors. The surgeons' self-rated self-esteem was work-related. Surgeons' Quality of Work Life was best predicted by Physician Empathy but also their self-rated Self-Esteem contributed significantly to the prediction. Surgeons' MIL-P was significantly predicted by Physician Empathy and State Anxiety.
CONCLUSION
Surgeons' current personality attributes might not apply to all of them. Female surgeons were more empathetic and felt more presence of meaning in life than male surgeons, and men were less anxious than female surgeons. Junior trainees experienced less anxiety than senior trainees but were more stressed than consultants. The most significant predictors of surgeons' personality were their experience of presence of meaning in life along with their level of empathy.